Understanding community's behavioral responses towards Covid-19: Who comply, who don't and reasons of incompliance - Dyah Anantalia Widyastari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2020)
Perspectives: *) Behavioral responses towards Covid-19 measures: who comply, who donot and reasons of incompliance *) Has the government convey the right messages to the public?